PENGARUH DANA PIHAK KETIGA, LIKUIDITAS PENDANAAN DAN RISIKO KREDIT TERHADAP PENYALURAN KREDIT BANK SAAT COVID-19 DI INDONESIA - Amril Muharyadi; Etty Gurendrawati; Dwi Handarini (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
One of the sectors affected by the COVID-19 pandemic is the banking industry, where social and economic restrictions imposed to control the spread of the virus have impacted various aspects of bank operations, especially lending. In this scenario, banks face new challenges in maintaining liquidity, managing credit risk, and ensuring continuous lending to customers in need. Thus, this study aims to analyze the extent to which specific factors, such as third-party funds, funding liquidity, and credit risk, influence lending by banks in Indonesia during the COVID-19 pandemic. The research method employed is a quantitative approach involving panel data regression analysis. This approach enables researchers to explore the cause-and-effect relationships among the variables under scrutiny. The data utilized consists of secondary data from banks categorized as BUKU III and BUKU IV, representing a certain size and complexity of banks. The data was collected during the uncertain period of 2020-2021, marked by the pandemic's impact. The analysis revealed that third-party funds positively influence banks' lending during the COVID-19 pandemic. This implies that the greater the amount of third-party funds held by banks, the more likely they are to extend credit to customers. However, funding liquidity and credit risk exert a negative influence on lending. This suggests that lower funding liquidity and higher credit risk make it more challenging for banks to provide credit to customers during the pandemic.